Complement C1q as a Potential Biomarker for Obesity and Metabolic Syndrome in Chinese Adolescents - Yang, Xuelian; Ma, Yanan; Zhao, Zhongyi; Zhen, Shihan; Wen, Deliang (Frontiers in Endocrinology, 2020)
Abstract Background: Complement C1q (C1q) has been confirmed to be related to obesity, metabolic syndrome (MetS), and its components. However, human data regarding the associations are relatively scarce. This study aimed to investigate associations of C1q with obesity as well as MetS in Chinese adolescents. Methods: A total of 1191 Chinese adolescents aged 13-18 years were enrolled in this study. The biochemical and anthropometric variables of all the subjects were evaluated using standardized procedures. C1q was measured using the immunoturbidometric assay. The relationship between C1q and obesity or MetS was analyzed using multiple regression analyses. Results: Obesity was more prevalent among participants in the highest tertile than in the lowest tertile of C1q levels. The highest tertile of C1q was related to a greater effect on the risk of MetS, and its trend test was statistically significant. Except for hyperglycemia, the prevalence of other components of MetS significantly increased relative to an increase in C1q tertile. Receiver operating characteristic (ROC) curve analysis of C1q for predicting adolescents with MetS illustrated that the area under the curve (AUC) was 0.82 (95% confidence interval (CI): 0.76, 0.88; P<0.001) in the total population after adjusting for confounders. Conclusions: This study observed a significantly higher prevalence of obesity and MetS features in adolescents with high C1q. The findings of the current study also reported a significant relationship between C1q levels and MetS components (except for fasting plasma glucose (FPG)) in Chinese adolescents. C1q may represent a biomarker for predicting obesity or MetS in adolescents.